Therapeutic Journey and Economic Burden of Patients with Myasthenia Gravis in Italy: Results of a Real-World Analysis - Perrone, Valentina; Mazzoni, Stefania; Cappuccilli, Maria; Andretta, Margherita; Bacca, Marcello; Barbieri, Antonietta; Bartolini, Fausto; Chinellato, Alessandro; Ciaccia, Andrea; Costantini, Alberto; De Vita, Francesco; Dell'Orco, Stefania; et al. (Farmeconomia. Health Economics and Therapeutic Pathways, 2025)
AIM: This analysis investigated the population with Myasthenia Gravis (MG) in Italy, to describe epidemiology, mortality, patients’ characteristics, comorbidity profile, therapeutic management, and healthcare consumption and related costs.METHODS: From 2012 to 2021, MG patients were identified in administrative flows of healthcare entities through hospitalization discharge diagnosis or exemption code for MG or a pyridostigmine prescription. Medications and comorbidities were searched before inclusion and healthcare costs were analysed at 1-year follow-up. Epidemiology estimates were reported as cases/100,000 people, and mortality rates, stratified by age classes and gender, were assessed during 2019. MG patients were compared with age- and gender-matched subjects without MG.RESULTS: At the end of 2021, MG prevalence was 35.1/100,000 and incidence 4.7/100,000 people. Mortality in 2019 was 3.2% in overall MG sample, and tended to rise in males and elderly patients. About 90% received MG-related treatments, namely pyridostigmine, corticosteroids and immunosuppressants (81.3%, 76.9% and 26.1% of patients respectively). Unsurprisingly, the yearly healthcare resource consumption/patient was higher in MG patients than in non-MG subjects (p